Indigenous peoples in Brazil: obstacles to the realization of the land right - Fran Espinoza (Universidade de Santa Cruz do Sul, 2021)
The indigenous peoples' land rights are deprived from their effective realization although it is guaranteed in the Brazilian Federal Constitution of 1988 and in several international human rights documents. In this sense, the objective of this article is to analyze where they arise and what are the obstacles to the effectiveness of the land rights of indigenous peoples in Brazil. Thus, the sustained hypothesis is that: in the face of the regulation-ineffectiveness paradox, obstacles to the realization of the land rights are hidden under legal instruments bound to a desired social inefficiency. The method used in the present research is qualitative in nature, it was used bibliography specialized in the subject, besides texts and legal norms. It is concluded that the permanence of certain social and cultural legal mechanisms that hinder the realization of the right to land reveals the construction of an intended paradox between positivation and ineffectiveness of the indigenous peoples' territorial rights.